Energy for Freedom: reflexiones para el análisis crítico de proyectos de electrificación rural aislada - Ten-Palomares, M. (Revista Iberoamericana de Estudios de Desarrollo)
Energy is considered essential for Human Development. However, rural electrification projects rarely include rural population’s aspirations, especially indigenous people’s aspirations. Using the Technologies for Freedom approach from a multilevel perspective, we analyze a case study in the Ecuadorian Amazon. Through this approach, called Energy for Freedom, which is focused on expanding people’s freedoms, we explore how energy stakeholders’ development and energy visions are connected with Amazonian indigenous people’s aspirations. We argue that integrating the multilevel perspective to the analysis of technological development projects it is essential for the design of alternatives adapted to their diverse realities and to highlight the plurality of energy visions.